2022
DOI: 10.3390/pharmaceutics14020311
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Microbubbles with Homogeneous Ligand Distribution for Higher Binding Efficacy

Abstract: Phospholipid-coated targeted microbubbles are used for ultrasound molecular imaging and locally enhanced drug delivery, with the binding efficacy being an important trait. The use of organic solvent in microbubble production makes the difference between a heterogeneous or homogeneous ligand distribution. This study demonstrates the effect of ligand distribution on the binding efficacy of phospholipid-coated ανβ3-targeted microbubbles in vitro using a monolayer of human umbilical-vein endothelial cells and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…It was confirmed that the dissociation of MBs from both charged and uncharged surfaces was less pronounced at wall shear stress values up to 0.5 Pa, but occurred more rapidly from 0.5 Pa to 1 Pa for all formulations ( Figure 3 ). Phospholipid-coated ανβ3-targeted MBs used in endothelial cell targeting by Langeveld et al remained attached to their target under flow up to shear stress values of approximately 0.2 Pa [ 59 ]. There was a significant reduction in the number of bound MBs from approximately 0.5 Pa, which is consistent with levels of attachment and loss of cationic MBs under flow in this work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was confirmed that the dissociation of MBs from both charged and uncharged surfaces was less pronounced at wall shear stress values up to 0.5 Pa, but occurred more rapidly from 0.5 Pa to 1 Pa for all formulations ( Figure 3 ). Phospholipid-coated ανβ3-targeted MBs used in endothelial cell targeting by Langeveld et al remained attached to their target under flow up to shear stress values of approximately 0.2 Pa [ 59 ]. There was a significant reduction in the number of bound MBs from approximately 0.5 Pa, which is consistent with levels of attachment and loss of cationic MBs under flow in this work.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Langeveld et al also compared how the homogeneity of the ligand distribution affected MB binding. They showed that MBs with a more homogenous ligand distribution had a higher binding efficacy than those with a heterogenous distribution [ 59 ]; future work in this area could investigate how the arrangement of lipids in a cationic MB may also affect MB binding efficacy. In our investigation, both RAMBs + and NOMBs + were able to remain in contact or continue accumulating on the negatively charged surface up to wall shear stress values of 0.2 Pa and 0.5 Pa, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For contrast-enhanced molecular imaging applications, labeling consistency of ligands on the surface of the MB shell is important for the optimal target-binding performance of targeted MBs. Furthermore, ligand labeling distribution can be enhanced upon preferential use of phospholipid formulations and specific lipid handling methods prior to MB production [22,23]. Microfluidic devices allow precise control over these production parameters to achieve standardized methodologies of targeted MB synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Pioneering works of MB shell stabilization with albumin by Feinstein and Keller led to the regulatory approval of Albunex (Molecular Biosystems Inc., San Diego, CA, USA) MBs are colloidal systems with a mean diameter of 1-7 µm, acting as real blood pool agents. Beyond imaging applications, MBs are actively investigated as drug delivery systems due to their shell drug loading capacities and gaseous core US stimuliresponsiveness [10,[13][14][15][16]]. An MB shell is mainly stabilized with lipids, proteins, or polymers [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%